Oxidation and cracking/spallation resistance of ZrB2–SiC–TaSi2–Si coating on siliconized graphite at 1500 °C in air. Issue 5 (1st April 2020) - Ren, Yan; Qian, Yuhai; Xu, Jingjun; Jiang, Yan; Zuo, Jun; Li, Meishuan
Abstract: A ZrB2 –SiC–TaSi2 –Si coating on siliconized graphite substrate was prepared by a combination process of slurry brushing and vapor silicon infiltration. The high-temperature oxidation behavior and cracking/spallation resistance of the as-prepared coating were investigated in detail. It was revealed that the oxidation kinetics at 1500 °C in static air followed a parabolic law with a relatively low oxidation rate constant down to 0.27 mg/(cm 2 ·h 0.5 ). The crack area ratio of the as-prepared coating was determined as 3.8 × 10 −3 after severe thermal cycling from 1500 °C to room temperature for 20 times. Apart from the formation of ZrO2 as skeleton phase with SiO2 as infilling species, the good oxidation and cracking/spallation resistance of the coating also could be attributed to its unique duplex-layered structure, i.e., a dense ZrB2 –SiC–TaSi2 major layer filled with Si and an outermost Si cladding top layer. Meanwhile, the strong adhesion strength of the SiC transition layer with the graphite substrate and the outer ZrB2 –SiC–TaSi2 –Si layer was a vital factor as well.